A geografia escolar e a linguagem cartográfica no contexto da reforma do Ensino Médio, da BNCC e do DRC/MT: uma análise em uma escola pública de Nova Xavantina/MT - Nascimento, Marinalva Ferreira do (2024)
School Geography aims to contribute to the formation of conscious citizens, capable of understanding and analyzing the complex interactions between society and the environment, from a spatial context, and aiming at the imminence of active and responsible participation in social life. However, with the educational changes introduced by Law 13,415/2017 and the implementation of the National Common Curricular Base (BNCC), Geography teaching in High School faces quite concerning challenges, as changes in the curriculum matrix negatively affect the teaching-learning process of students, especially regarding geographical knowledge and cartographic language. In this context, this research aimed to analyze the presence and articulation of cartographic language in the teaching of Geography at a public school in Nova Xavantina, in the state of Mato Grosso, in light of the High School reform. The objectives include understanding the elements that influenced the reform, evaluating the impact of the BNCC on Geography teaching, analyzing the didactic material, and identifying the challenges faced by Geography teachers in the new educational context. Regarding methodology, the research is qualitative, with data collection using a focus group and a semi-structured questionnaire with High School Geography teachers, enabling an analysis of the pedagogical practice and the challenges faced from the perspective of the reform. In this scenario, we discussed some essential points, such as the reform implementation process that disregarded the precarious infrastructure of schools in the country; the way Geography is diluted into a large area, and the reduction of the workload of the Geography subject. We present a discussion that analyzes the presence of cartographic language in the BNCC of High School, highlighting the relevance of Cartography for Geography teaching. Additionally, an analysis was made of how cartographic language is integrated into the Geography content present in the High School didactic material of Mato Grosso, created by the Getúlio Vargas Foundation (FGV). Furthermore, we addressed the origin of Cartography and its function as an instrument of state power, as well as discussing cartographic language as an essential proposal for the development of students' geographical reasoning. In this context of investigating Geography teaching, with an emphasis on cartographic language, within the scope of the current High School reform in Brazil, the results reveal a panorama of regression in the geographical education of students and highlight the precariousness of public education. The conclusions highlight the challenges and impacts on teaching practice, contributing to the discussion about the need for improvement in educational policies